2016
DOI: 10.1159/000443263
|View full text |Cite
|
Sign up to set email alerts
|

Binasal Prong versus Nasal Mask for Applying CPAP to Preterm Infants: A Randomized Controlled Trial

Abstract: Background: Nasal continuous positive airway pressure (NCPAP) is being widely used for the treatment of respiratory distress syndrome (RDS) in preterm infants. However, there are only a few studies which compare different interfaces of NCPAP delivery and their effects on respiratory outcomes. Objective: We aimed to determine whether NCPAP applied with binasal prongs compared to that with a nasal mask (NM) reduces the rate of moderate/severe bronchopulmonary dysplasia (BPD) in preterm infants. Methods: Infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 27 publications
3
52
1
Order By: Relevance
“…In this particular analysis, a significant heterogeneity (I 2 75%, P for χ 2 0.02) was identified (figure 2). A sensitivity analysis performed after excluding one trial showed reduced heterogeneity (I 2 46%, P for χ 2 0.17) 5. This trial showed significant lower association of moderate to severe CLD in infants receiving mask NCPAP compared with infants binasal prongs NCPAP (14.6% vs 2.7%, P 0.01) 5.…”
Section: Summary Of Evidencementioning
confidence: 85%
See 2 more Smart Citations
“…In this particular analysis, a significant heterogeneity (I 2 75%, P for χ 2 0.02) was identified (figure 2). A sensitivity analysis performed after excluding one trial showed reduced heterogeneity (I 2 46%, P for χ 2 0.17) 5. This trial showed significant lower association of moderate to severe CLD in infants receiving mask NCPAP compared with infants binasal prongs NCPAP (14.6% vs 2.7%, P 0.01) 5.…”
Section: Summary Of Evidencementioning
confidence: 85%
“…Only one trial included extremely preterm infants below <26 weeks’ GA 3. The NCPAP systems varied across the trials: three trials used infant flow devices,3 4 6 two trials used bubble NCPAP1 2 and one trial used ventilator NCPAP 5. In the four trials evaluating the primary outcome (endotracheal ventilation/NCPAP failure), the use of caffeine was prophylactic in three trials2 3 5 and therapeutic in one trial 1.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…We prefer nasal-mask CPAP because it is easier to care for, delivers a more stable CPAP and is more comfortable for the infants than nasal prongs. Using nasal masks has been shown to shorten the duration on CPAP compared to nasal prongs [21]. Infants weighing <750 g were excluded because the appropriate nasal cannula size was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Using a flow driver to generate CPAP has the theoretical advantage of offloading expiratory work of breathing (the Coanda effect), although no important clinical differences have been shown among devices used to deliver CPAP, but the simplicity of bubble CPAP systems allows their use in low-income settings [94]. Trials comparing interfaces show no differences between nasal prongs and short pharyngeal tubes for initial stabilisation in the delivery room [50], but for prolonged use nasal masks may be most effective [95]. All CPAP interfaces carry a risk of facial distortion and nasal trauma.…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%